State Administrative Law and Citizens’ Rights - Situmeang, Harry Prayudha; Klose, Rojer Al; Rizki, Sefiadil (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research examines the role of State Administrative Law (Hukum Administrasi Negara/HAN) as a fundamental instrument for protecting citizens’ rights against government actions. In the context of Indonesia as a state based on the rule of law, governmental authority is not merely an expression of executive power but must be exercised in accordance with the principles of legality, accountability, transparency, and respect for human rights. State Administrative Law serves as a legal framework that regulates relations between the government and citizens to prevent abuses of power and ensure legal certainty and justice. This study employs a normative juridical approach by analyzing laws and regulations, judicial decisions, and institutional practices related to state administrative governance. The analysis focuses on control mechanisms provided by HAN to supervise government administrative actions. The findings indicate that HAN offers several legal remedies and oversight instruments, including administrative objections, proceedings before the State Administrative Court (Pengadilan Tata Usaha Negara), and supervision by independent bodies such as the Ombudsman. These mechanisms are intended to ensure that government decisions comply with legal norms and do not violate citizens’ rights. Nevertheless, the effectiveness of State Administrative Law still faces challenges, including low public legal awareness, overlapping regulations, bureaucratic complexity, and weak institutional oversight. Consequently, access to justice in administrative disputes remains limited. Therefore, this research highlights the need for institutional reform, simplification of administrative procedures, regulatory harmonization, and stronger public participation to optimize the role of HAN in supporting good governance in Indonesia.